IMPLEMENTASI METODE RAPID APPLICATION DEVELOPMENT DALAM MEMBANGUN E-COMMERCE DI BIDANG UKM - Riyanto, Verry (LPPM Universitas Nusa Mandiri, 2017)
The method used by the author with several steps starting from data collection, observes, interviews, library research approach to RAD in building market place based website, then make ERD and make UML, tools-tools that use the Entity Relational Diagram and Unified Modeling Language. Of the existing problems are still many businesses are SMEs that have not implemented information systems, the authors tried to examine the system of information on the SME market place. With the development of computerized services into web-based systems, the writer hopes the problems that exist in the various SMEs, especially in terms of the purity of the data can be overcome with good. The information generated can be more accurate, faster and more efficient. In addition to the information systems are built for SMBs based websites become a benchmark of the development of SMEs in the digital world in the wider community. So that everything could be run more efficiently and effectively.